Design of an Arduino Uno-based Drain Cleaning System for Housing Clusters - Mahardika, Joar Yahdi; Anshory, Izza; Sulistiyowati, Indah; Rasjid Saputra, Dwi Hadidjaja (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
The Design of a Drain Cleaning System in an Arduino Uno-based Housing Cluster is a research that aims to overcome the problem of obstacles in closed drainage channels in housing clusters. This research uses a design approach and implementation of an Arduino Uno microcontroller-based system integrated with ultrasonic sensors, buzzers, relays, and AC motors. The analysis method involves observation, literature study, problem analysis, solution, and conclusion. Testing is done through measuring the response of the components, the performance of the AC motor, and evaluating the entire system. The results show that the system is able to detect, measure, and overcome obstacles in drainage channels effectively. This research is expected to contribute to improving the quality of the residential environment and solving the problem of frequent flooding. By limiting the development of one unit of drainage channel cleaning tool for one house in a housing cluster, where each house will be equipped with one unit of tool installed on the water channel in front of its house. The conclusion of this research is that the system design can be an efficient and responsive solution in maintaining the smooth flow of water in the housing cluster, as well as providing convenience for residents to maintain their environment.